Destabilization of the Organized Structure of Ventricular Fibrillation During Reperfusion - M. I. Gurianov; P. K. Yablonsky (Общая реаниматология, 2023)
Aim: to study the effect of reperfusion on the organized frequency-amplitude structure of ventricular fibrillation (VF) in the dog heart.Materials and methods. We conducted 4 experiments on 8 dogs. In each experiment, the isolated heart of one dog was perfused with the blood of the second (supporting) dog. In 4 experiments on an isolated artificially perfused heart, 6 episodes of 3 min ischemia and 10 min reperfusion of the heart were performed in VF (1–2 episodes of ischemia-reperfusion in one experiment). Each episode of 3 min ischemia in VF was preceded by a 10 min perfusion of the heart in VF. Ventricular electrogram was recorded during VF episodes. A frequencyamplitude (spectral) analysis of 1 sec segments of the electrogram was performed, and the proportion (in %) of 0.5–15 Hz frequency oscillations in 10 sec segments of the electrogram was determined in 6 episodes of perfusion, ischemia and reperfusion in VF (M±m, N=60). The VF frequency-amplitude structures during ischemia and reperfusion were compared with the stable VF frequency-amplitude structure during perfusion taken as the control. The nonparametric Welch criterion in the «The R Project for Statistical Computing» software environment was used to compare the VF parameters during perfusion, ischemia and reperfusion. Results. 9–10 Hz frequency oscillations dominated in the VF frequency-amplitude structure during heart perfusion, taken as the control. In the first 30 sec of ischemia, the frequency and amplitude of the dominant oscillations did not significantly change vs VF control obtained during cardiac perfusion. A decrease of dominant oscillations frequency up to 6.5–7.5 Hz, and of the proportion of oscillations — up to 26% was documented at the 3rd min of ischemia. At the 1st min of reperfusion, the frequency of dominant oscillations increased to 13.5–14.5 Hz, but the proportion of oscillations remained reduced to 26%, as at the 3rd min of ischemia. At the 2nd min of reperfusion, the frequency of dominant oscillations decreased to 9.5–10.5 Hz, and the proportion of dominant oscillations increased to 33%. The frequency and amplitude of the dominant oscillations stabilized at 3–10 min of reperfusion: oscillations at 9–10 Hz frequency accounted for 32–33% of the spectral power.Conclusion. Reperfusion in VF is characterized by transient destabilization of VF organized structure at the 1st min of the procedure. VF organized structure regains stabilization within 2–10 min of reperfusion. Cardiac perfusion in intentionally induced VF can be used instead of cardioplegia during major cardiac surgery to boost cardiac resistance to ischemia and prevent or reduce reperfusion complications.